THE GENETIC AND BEHAVIOURAL UNDERPINNINGS OF NATURAL VARIATION IN SOCIAL BEHAVIOUR - Scott, Andrew M. (My University, 2021)
A rich diversity of social behaviours exists in the animal kingdom, and these behaviours have evolved to perform a variety of adaptive functions. Social behaviours show variation both among and within species, however the mechanisms that give rise to this variation are not well understood. Using fruit flies (Drosophila melanogaster), my goal was to uncover the genetic and behavioural mechanisms that underpin natural variation in two different social behaviours: sociability and sexual aggression. First, I showed that sociability, which is the tendency of animals to engage in friendly activities together, is influenced by indirect genetic effects (IGEs), and that encounters among individuals drive these effects (Chapter 2). I then showed that sociability and social plasticity have low-moderate heritability (Chapter 3), and sociability is not correlated between the sexes or with activity. I then generated lineages of flies with high and low sociability using artificial selection (Chapter 4). The evolved lineages had significantly diverged sociability which was not associated with fitness measures or nearest-neighbor distances, but was negatively correlated with intrasexual aggression (Chapter 4). Finally, in sexual aggression, which I quantified as male forced copulation rate, I showed that evolved differences and differences due to social plasticity were both associated with the differential expression of many genes, but only a few of these genes were significant in both (Chapter 5). I also showed that these sets of genes are enriched in neuropeptide hormone and serotonin gene ontology categories, and that 4 of 7 chosen genes were validated for their effects on sexual aggression. Overall, this thesis sheds light on the complex mechanisms that underlie variation in these social behaviours, and it paves the way for future research to further elucidate some of these mechanisms, especially on the genetic basis of sociability using the evolved lineages I generated.
THE GENETIC AND BEHAVIOURAL UNDERPINNINGS OF SOCIAL BEHAVIOUR
Keywords: Social behaviour; Sociability; Fruit flies; Drosophila; Sexual aggression; Aggression; Indirect genetic effects; Artificial selection; Heritability; Social plasticity; RNAseq; Differential expression; Forced copulation; Genetic correlation